(untitled) (USA, 1999)
Information incorporated in this volume is of nature that could be valuable in making decisions in this field: characteristics of construction materials, environment control, livestock housing design, silage storage, equipment and waste management, and draught animals husbandry.
Keywords: Agricultural Engineering,Aquacultural engineering,Kỹ thuật nông nghiệp